Developments in Gigascale Silicon Optical Modulators Using Free Carrier Dispersion Mechanisms. (25th May 2008) - Basak, Juthika; Liao, Ling; Liu, Ansheng; Rubin, Doron; Chetrit, Yoel; Nguyen, Hat; Samara-Rubio, Dean; Cohen, Rami; Izhaky, Nahum; Paniccia, Mario
Abstract : This paper describes the recent advances made in silicon optical modulators employing the free carrier dispersion effect, specifically those governed by majority carrier dynamics. The design, fabrication, and measurements for two different devices are discussed in detail. We present an MOS capacitor-based modulator delivering 10 Gbps data with an extinction ratio of∼ 4 dB and a pn-diode-based device with high-speed transmission of 40 Gbps and bandwidth greater than 30 GHz. Device improvements for achieving higher extinction ratios, as required for certain applications, are also discussed. These devices are key components of integrated silicon photonic chips which could enable optical interconnects in future terascale processors.